Shenqifuzheng injection inhibits lactic acid-induced cisplatin resistance in NSCLC by affecting FBXO22/p53 axis through FOXO3 - Wei Bo; Xiaokai Wang; Ning Yu; Chun Wang; Chunying Liu (Respiratory Research, 2024)
Highlights FOXO3 was decreased, while LA and FBXO22 were increased in NSCLC patients. LA promoted cisplatin resistance in NSCLC in vitro and in vivo. SQFZ inhibited LA-induced cisplatin resistance in NSCLC by regulating FOXO3. FBXO22 affected p53 ubiquitination to reverse the inhibitory effect of SQFZ. SQFZ inhibited cisplatin resistance in NSCLC by FOXO3/FBXO22/p53 axis.